Orlovi rano lete - Jovanović, Soja (Yugoslavia : Avala Film Beograd, 1964)
The film celebrates the contribution of Yugoslav children to the partisan struggle in WWII. The film is an screen adaptation of the novel by Serbian writer Branko Čopić. Just before the beginning of WWII, in the mountainous region of Serbia, a group of pupils, dissatisfied with their strict village teachers decide to turn into “hajduks” – the name by which autonomous outlaws from the Turkish times were known – and live in the woods. The first part of the movie portrays the adventures of this group of youngsters, revolving mainly around the wooden hut which they construct to provide themselves with a safe hideout when playing truant. However, once the war starts, the young “hajduks” need to grow up fast. As the fighting approaches their homes, their innocent childish game turns serious and soon they are fighting and trying to help their village and nearby partisans. In the same hut where they used to hide from their school teacher, the young “hajduks” now hide from the enemy. In the moralizing and happy finale, they manage to trick them and steal ammunition, thus providing the partisans with a crucial advantage that brings victory in an important battle.
Keywords: Fiction films